Estimate the demand for a product family with a discrete choice model - Lian Lim, Philips (2014)
With the growing diversification in consumer life styles and needs, organizations are increasingly competing in coming up with product lines instead of focusing on a single product; in expectation to cover a broader range of market segments. However, putting too many products in a product line may bring more damage than benefit to the company hence it is essential for manufacturers to know their optimal product line.